2016
DOI: 10.1021/acs.bioconjchem.6b00213
|View full text |Cite
|
Sign up to set email alerts
|

Two for the Price of One: PAMAM-Dendrimers with Mixed Phosphoryl Choline and Oligomeric Poly(Caprolactone) Surfaces

Abstract: The application of dendrimers for biological and medical purposes is highly dependent on the type of surface group in relation to cytotoxicity. Since amine terminated PAMAM dendrimers have been shown to have toxic properties and thereby limited applications in the medical field, the discovery of a new nontoxic surface coating is of great interest. In the present work, amine terminated DAB-PAMAM dendrimers from generation zero to four have been coated with statistical surface functionalization giving a dendrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Dendrimer PPI generations 1–5 with primary amine groups at their surfaces were applied as scaffolds for multimeric presentation of PC. Dendrimers modified with PC groups by other synthetic routes have been reported previously. , However, fully derivatized dendrimer products have not been obtained. Here, we utilized the commercially available PC compound 2-methacryloyloxyethyl phosphorylcholine (MPC) to introduce PC groups onto the dendrimer surface amines.…”
Section: Resultsmentioning
confidence: 99%
“…Dendrimer PPI generations 1–5 with primary amine groups at their surfaces were applied as scaffolds for multimeric presentation of PC. Dendrimers modified with PC groups by other synthetic routes have been reported previously. , However, fully derivatized dendrimer products have not been obtained. Here, we utilized the commercially available PC compound 2-methacryloyloxyethyl phosphorylcholine (MPC) to introduce PC groups onto the dendrimer surface amines.…”
Section: Resultsmentioning
confidence: 99%
“…The linker benzyl 6‐hydroxyhexanoate was prepared from ϵ‐caprolactone over two steps in 90 % yield (SI) [20] . N ‐Acetylglucosamine was reacted with acetyl chloride to afford glycosyl chloride 6 in 70 % yield (SI) [21] .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the widespread use of dendrimers in pharmaceutics and biomedicine, its complex basic features, such as toxicity due to the existence of a terminal NH2 group on the surface of dendrimer and fast clearing of dendrimer from the blood stream amid cancer treatment, restrain their function in the treatment of cancer [ 90 , 91 , 92 ]. Various studies have shown that the toxicity of dendrimers is influenced by their generation (size), development time, concentration, and the sort of terminal group on their exterior [ 93 , 94 , 95 , 96 ].…”
Section: Dendrimer Nanoparticulate Ddsmentioning
confidence: 99%